Retrospective observational study of chloral hydrate use in mechanically-ventilated pediatric intensive care unit (PICU) patients 2012–2017 - Ettinger, Nicholas A.; Kiskaddon, Amy; McNeely, Lindsay; Craycraft, Justin; Rogers, Amber; Achuff, Barbara-Jo; Guffey, Danielle; Musick, Matthew (Frontiers in Pharmacology, 2023)
Chloral hydrate (CH) has long been utilized as a pediatric procedural sedation agent. However, very little is published describing CH use in a pediatric intensive care unit (PICU) setting. The aim of this retrospective observational cohort study was to investigate and describe the use of CH in mechanically-ventilated, critically ill children at a large pediatric tertiary referral hospital. Data were extracted from the hospital electronic medical record and a locally maintained registry of all children admitted to the PICU between 2012 and 2017. Patients admitted to the cardiovascular ICU were not included in this review. The clinical and pharmacy data for 3806 consecutive PICU admissions of mechanically-ventilated, critically ill children were examined. 283 admissions received CH during their first ICU stay. CH-exposed children were younger (16 months vs. 35 months, p<0.001), the median total dose of CH (indexed to duration of ventilation) was 11 mg/kg/day, the median time to first CH dose was 3 days and more CH doses were administered at night (1112 vs. 958, p<0.001). We constructed a propensity score to adjust for the differences in patients with and without CH exposure using logistic regression including variables of age, sex, diagnosis, and PRISM3 score. After adjustment, the median length of mechanical ventilation was 5 days longer in the CH-exposed group (95% Confidence Interval [CI] 4-6) compared to unexposed CH patients. Similarly, the median length of ICU duration was 9.4 days longer (95% CI 7.1-11.6) and median length of hospital admission duration was 13.2 days longer (95% CI 7.8-18.6) in CH-exposed patients compared to CH-non-exposed. After adjustment, CH-exposed patients had a 9% higher median exposure to HFOV (95% CI 3.9-14.6), but did not have higher median exposures to new tracheostomy (95% CI -0.4-2.2) or ECMO (95% CI -0.2-5.0). As part of an extended sedation regimen in mechanically-ventilated and critically ill children, CH is associated with somewhat higher complexity of illness and longer ICU durations.